RANCANG BANGUN PENERAPAN MODEL PROTOTYPE DALAM PERANCANGAN SISTEM INFORMASI PENCATATAN PERSEDIAAN BARANG BERBASIS WEB - Jehan Saptia Kurnia; Fitria Risyda (Fakultas Ilmu Komputer dan Desain - Unsurya, 2021)
ABSTRACTThe use of information system technology becomes very useful for companies that need an accurate, reliable, fast, relevant and detailed information flow. Information System inventory of Good can increase productivity and good performance for the company. Based on the description above, it is very important to provide an inventory information system so that the company's performance is getting better.Inventory recording at PT. ABC currently using a computer with software Ms.Excel for data processing but in the process sometimes found mistake like data redundancy, incompatibility of stock items with records and providing long reports because data validation is needed first. Inventory Information System Design is built based on the website with the Prototype method. The design of the information system uses PHP and HTML and MySQL as the database. The design of system is expected to improve performance especially those related to processing inventory data to making inventory reports at PT.ABCÂ Key words : Information System, Inventory, Prototype Methode